USE OF GAS BURNERS TYPE "DAVA" OPERATING UNDER VARIABLE LOAD TO PRODUCE HEAT AND HOT WATER - Daud V. (Problems of the Regional Energetics)
The article brings additional information referred to upgraded gas burners type "DAVA", which are characterized by high performance at variable load. Adaptation of burner operation is carried out automatically. There are presented design features that allow increase of the efficiency and the reliability of these burners at variable load, and reducing natural gas consumption. The range of variation of the coefficient of excess air affects the efficiency of the burner. The experimental results of the tests of gas burners of different power had confirmed the economic effect of the upgraded burners at heat production. It is proved that economic effect increases with increasing of burner output and of operation time during the season.